Published endodontic articles in PubMed-indexed journals from Iran - Asgary, Saeed; Sabbagh, Sedigeh; Eghbal, Mohammad Jafar (Iranian Endodontic Journal, 2011)
Introduction: <span style="color: black; font-style: normal; font-family: ";Cambria";,";serif";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-fareast-language: ZH-CN; mso-bidi-language: FA;"> <span style="color: black; font-style: normal; font-family: ";Cambria";,";serif";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-fareast-language: ZH-CN; mso-bidi-language: FA;">The<span style="color: black; font-style: normal; font-family: ";Cambria";,";serif";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-fareast-language: ZH-CN; mso-bidi-language: FA;"> <span style="color: black; font-style: normal; font-family: ";Cambria";,";serif";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-fareast-language: ZH-CN; mso-bidi-language: FA;">aim of this survey was to illustrate statistical information about endodontic research published in pubmed index journals from the different universities of Iran. Materials and Methods: A PubMed search was performed to retrieve the endodontic publications of authors affiliated to different universities of Iran. Abstracts were reviewed and unrelated articles were omitted. Citation of each article was obtained from Scopus and Google scholar databases. Data were extracted and transferred to Microsoft Excel to determine the related scintometric indicators. Results: A total of 307 papers were found according to the defined criteria which shows considerable increase from 2 papers in 1992 to 54 in 2011. Majority of the papers (48%) were related to in vitro studies; this number was 33% for in vivo surveys. Meta-analysis, systematic review and clinical trial constituted 10% of all publications. The average number of authors for the overall publications was 3.84; majority of articles (20%) were written by three authors. The average number of citation from Google Scholar (8.93) was higher than those from Scopus (4.74). Most of the endodontic articles originated from the Mashad University of Medical Sciences (16%). <span style="font-size: 11pt; color: black; font-style: normal; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: ZH-CN; mso-bidi-language: FA; mso-ansi-language: EN-US;">Conclusion:<span style="font-size: 10pt; color: black; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-ansi-language: EN-US;"> Endodontic publication from different universities in Iran has considerably in creased, showing that research in becoming more important.